A Novel, Orally Bioavailable, Small-Molecule Inhibitor of PCSK9 With Significant Cholesterol-Lowering Properties In Vivo - Alexandra K. Suchowerska; Geurt Stokman; James T. Palmer; Phillip A. Coghlan; Elsbet J. Pieterman; Nanda Keijzer; Gilles Lambert; Kevin Chemello; Ali K. Jaafar; Jasneet Parmar; Liping Yan; Yingtao Tong; et al. (Journal of Lipid Research, 2022)
Proprotein convertase subtilisin kexin type 9 (PCSK9) inhibits the clearance of low-density lipoprotein (LDL) cholesterol (LDL-C) from plasma by directly binding with the LDL receptor (LDLR) and sending the receptor for lysosomal degradation. As the interaction promotes elevated plasma LDL-C levels, and therefore a predisposition to cardiovascular disease, PCSK9 has attracted intense interest as a therapeutic target. Despite this interest, an orally bioavailable small-molecule inhibitor of PCSK9 with extensive lipid-lowering activity is yet to enter the clinic. We report herein the discovery of NYX-PCSK9i, an orally bioavailable small-molecule inhibitor of PCSK9 with significant cholesterol-lowering activity in hyperlipidemic APOE∗3-Leiden.CETP mice. NYX-PCSK9i emerged from a medicinal chemistry campaign demonstrating potent disruption of the PCSK9-LDLR interaction in vitro and functional protection of the LDLR of human lymphocytes from PCSK9-directed degradation ex vivo. APOE∗3-Leiden.CETP mice orally treated with NYX-PCSK9i demonstrated a dose-dependent decrease in plasma total cholesterol of up to 57%, while its combination with atorvastatin additively suppressed plasma total cholesterol levels. Importantly, the majority of cholesterol lowering by NYX-PCSK9i was in non-HDL fractions. A concomitant increase in total plasma PCSK9 levels and significant increase in hepatic LDLR protein expression strongly indicated on-target function by NYX-PCSK9i. Determinations of hepatic lipid and fecal cholesterol content demonstrated depletion of liver cholesteryl esters and promotion of fecal cholesterol elimination with NYX-PCSK9i treatment. All measured in vivo biomarkers of health indicate that NYX-PCSK9i has a good safety profile. NYX-PCSK9i is a potential new therapy for hypercholesterolemia with the capacity to further enhance the lipid-lowering activities of statins.